Pengaruh kepimpinan instruksional dan hubungannya dengan komitmen dan efikasi guru sekolah gred A dan B di Kota Kinabalu: Satu tinjauan - Kasmah, Abdullah (2010)
This study was conducted to determine the perceptions of male and female teachers on instructional leadership of headmasters at five schools around Kota Kinabalu, Sabah. Relationship between instructional leadership of headmasters with teacher commitment and efficacy are also reviewed. The independent variables of this study is the five dimensions of headmaster instructional leadership that is; defining and disseminating information of schools, managing curriculum and teaching, promoting a positive learning environment, monitoring and giving feedback to teachers, assessing learning program. Dependent variable is the commitment and teacher efficacy. A sample of 70 teachers in Sk Rampayan, Sk Bukit Padang, Sk Tobobon, Sk Malawa and Sk Malangang Baru. Data collected through the distribution of the questionnaire used by the Lahui-Ako (1998) in research in Papua New Guinea, adapted from the 'Principal Instructional Management Rating Scale' (PMRS) by Hallinger and Murphy (1985). While the instrument for commitments is 'Diagnostic Assessment of school and principal Effectiveness', (Ebmeier, 1990) and efficacy instrument is 'Teacher Efficacy Scale' designed by Gibson and Dembo (1984). Data were analyzed using mean, standard deviation, t-test, one-way Anova test and Pearson correlation. The findings show that there is a correlation between the instructional leadership of headmasters with teacher commitment and efficacy of both grade schools A and B